An adaptive MIMO architecture for perceptually coded multimedia transmission through wireless channels - Buddha, Sreenivas Kartik (2010)
The public’s demand for wireless multimedia is stimulating research for efficient paradigms for the transmission of visual information over wireless channels which often suffer from multipath fading, shadowing and inter-symbol interference. The aim of this project is to implement a transmission scheme for images across a wireless channel, by capitalizing on the unequal importance attributed to different fragments of the image by the end user. Using the Human Visual System (HVS) of texture masking, the image to be transmitted is split into streams of different qualities. The highest quality stream which has low amount of texture in it is more sensitive towards noise whereas the lowest quality stream which has high texture content is relatively less noise sensitive. The motivation behind this project is to take advantage of this trait in order to develop an efficient architecture. Recent technologies like Orthogonal Frequency Division Multiplexing (OFDM), Multiple-Input Multiple-Output (MIMO), Adaptive Modulation and Coding (MAC) and Dynamic Channel Allocation (DCA) improve the spectrum efficiency of wireless systems especially in broadband applications. The communication architecture addressed here encompasses principles from the above technologies and tries to prioritize the data from high quality streams over data from low quality streams, so that the overall perceptual quality of the received image is enhanced. The simulations performed on the Lena and baboon test images demonstrate that the received images have indeed better perceptual quality in the case when the above perceptual model is adopted when compared to a normal transmission scheme.